2013
DOI: 10.1088/0004-637x/778/1/52
|View full text |Cite
|
Sign up to set email alerts
|

A Measurement of the Kinetic Sunyaev-Zel'dovich Signal Toward Macs J0717.5+3745

Abstract: We report our analysis of MACS J0717.5+3745 using 140 and 268 GHz Bolocam data collected at the Caltech Submillimeter Observatory. We detect extended Sunyaev-Zel'dovich (SZ) effect signal at high significance in both Bolocam bands, and we employ Herschel-SPIRE observations to subtract the signal from dusty background galaxies in the 268 GHz data. We constrain the two-band SZ surface brightness toward two of the sub-clusters of MACS J0717.5+3745: the main sub-cluster (named C), and a sub-cluster identified in s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
122
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(131 citation statements)
references
References 92 publications
9
122
0
Order By: Relevance
“…We speculate that the V-shape could be related to a bullet-like structure seen under a large projection angle. This would also explain the lack of an offset between the X-ray gas, dark matter, and galaxiesand is consistent with the large radial velocity component and the detected kinetic SZ signal (Mroczkowski et al 2012;Sayers et al 2013). Interestingly, the radio filament above R4 is aligned with the V-shape and is located immediately to the south of it.…”
Section: Merger Scenariosupporting
confidence: 69%
See 1 more Smart Citation
“…We speculate that the V-shape could be related to a bullet-like structure seen under a large projection angle. This would also explain the lack of an offset between the X-ray gas, dark matter, and galaxiesand is consistent with the large radial velocity component and the detected kinetic SZ signal (Mroczkowski et al 2012;Sayers et al 2013). Interestingly, the radio filament above R4 is aligned with the V-shape and is located immediately to the south of it.…”
Section: Merger Scenariosupporting
confidence: 69%
“…A study of the Sunyaev-Zel'dovich (SZ) effect provided further evidence for the presence of shock-heated gas (Mroczkowski et al 2012). Mroczkowski et al (2012) and Sayers et al (2013) found evidence for a kinetic SZ signal for one of the subclusters, confirming the large velocity offset (≈3000 km s −1 ) found earlier from spectroscopy data (Ma et al 2009). A recent study reported the detection of a second kinetic SZ component belonging to another subcluster (Adam et al 2016).…”
Section: Introductionmentioning
confidence: 52%
“…The shocks are probably produced by the near simultaneous merging of several large clusters. This merging geometry can, in principle, be understood better through observations of the kinetic Sunyaev-Zeldovich effect of the gas in the cluster as this is proportional to the velocity along the line of sight (Sayers et al 2013;Mroczkowski et al 2012). Analysis of X-ray data confirms the extreme nature of this cluster with temperatures in excess of 20 keV, making this cluster one of the hottest known so far.…”
Section: Discussionmentioning
confidence: 99%
“…At microwave wavelengths, this cluster is a bright Sunyaev-Zeldovich effect source (Mroczkowski et al 2012) which has enabled an estimate of its radial velocity through the Doppler shift induced by the plasma in the cluster to the photons of the cosmic microwave background (Sayers et al 2013). In the optical, a filament of galaxies seems to extend over cosmic scales from the centre of this cluster (Ebeling, Barrett & Donovan 2004;Medezinski et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the work of Hand et al (2012) constitutes the first clear detection of the kSZ effect (using the "pairwise" momentum approach that we describe below), and no other group has confirmed their results to date. In addition, Sayers et al (2013) have provided a first claimed detection of the kSZ effect in a single source. After the first data release of the Planck mission, some disagreement has been claimed between the cosmological frame set by Planck and measurements of peculiar velocities as inferred from redshift space distortions (Macaulay et al 2013).…”
Section: Introductionmentioning
confidence: 99%